Perlindungan Konsumen dalam Kasus Gagal Bayar Polis Asuransi Jiwasraya: Analisis Regulasi dan Peran OJK - Dhea Salsa Fadhila; Rahma Rini Khalisa Firdausi; Chammelia Annastasya Melati; Arifa Sholekhah; Sofia Nurul Toyiba; Muhammad Natasyah Fikko Artama (Lembaga Pengembangan Kinerja Dosen, 2025)
The policy default case by PT Asuransi Jiwasraya caused widespread unrest among the public and became an important precedent in assessing the effectiveness of legal protection for consumers in the financial services sector, especially life insurance. This research aims to analyze the form of legal protection provided to consumers, identify the regulations governing it, and evaluate the role of the Financial Services Authority (OJK) in supervising and handling the default case. The method used is a normative juridical approach by analyzing laws and regulations, legal doctrines, and court decisions, and supported by literature reviews from various scientific journals. The results show that although the regulatory framework governing consumer protection in the insurance sector is quite complete, such as Law Number 40 of 2014 concerning Insurance and Law Number 8 of 1999 concerning Consumer Protection, its implementation is still weak. OJK's role as a supervisor has proven to be not optimal, both in early detection of Jiwasraya's financial crisis and in taking action against violations of the prudential principle by company management. The conclusion of this study states that legal protection of consumers in the Jiwasraya case has not been functionally effective, and needs to be strengthened through supervisory reform and regulatory improvement. This research is expected to contribute to the formulation of policies and the improvement of the consumer protection system in the future.